Soybean SDS in South Africa is Caused by Fusarium brasiliense and a Novel Undescribed Fusarium sp - Tewoldemedhin, Yared T (Plant disease, 2017)
Soybean sudden death syndrome (SDS) was detected in South Africa for the first time during pathogen surveys conducted in 2013 to 2014. The primary objective of this study was to characterize the 16 slow-growing Fusarium strains that were isolated from the roots of symptomatic plants. Molecular phylogenetic analyses of a portion of translation elongation factor 1-α (TEF1) and the nuclear ribosomal intergenic spacer region (IGS rDNA) indicated that the etiological agents were Fusarium brasiliense and a novel, undescribed Fusarium sp. This is the first report of F. brasiliense outside of Brazil and Argentina and the novel Fusarium sp. causing soybean SDS. Koch's postulates were completed for both fusaria on seven soybean cultivars that are commercially available in South Africa. Results of the pathogenicity experiment revealed that the strains of F. brasiliense and Fusarium sp. differed in aggressiveness to soybean, as reflected in differences in foliar symptoms, root rot, and reduction in shoot length. Cell-free culture filtrates of the two soybean SDS pathogens from South Africa and two positive control strains of F. virguliforme from the United States induced typical SDS symptoms on susceptible soybean cultivars in a whole-seedling assay, indicating that they contained phytotoxins